2022
DOI: 10.3389/fgene.2022.948505
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study for systemic lupus erythematosus in an egyptian population

Abstract: Systemic lupus erythematosus (SLE) susceptibility has a strong genetic component. Genome-wide association studies (GWAS) across trans-ancestral populations show both common and distinct genetic variants of susceptibility across European and Asian ancestries, while many other ethnic populations remain underexplored. We conducted the first SLE GWAS on Egyptians–an admixed North African/Middle Eastern population–using 537 patients and 883 controls. To identify novel susceptibility loci and replicate previously kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 104 publications
0
2
0
Order By: Relevance
“…DOCK10, dedicator of cytokinesis 10, belongs to a cytokinesis protein family, whose members are guanosine nucleotide exchange factors for Rho GTPases. It has been confirmed as a SLE locus (rs11462616) in an Egyptian population [24]. Sheng et al [25] suggested that overexpression of the transcriptional regulator BACH2 represses Th9 cell differentiation by suppressing IRF4 expression in SLE patients, and that it might be a potential target for SLE treatment.…”
Section: Association Of Up-dppgcs In Pla-ko1l3 With Sle In the Gwas C...mentioning
confidence: 98%
“…DOCK10, dedicator of cytokinesis 10, belongs to a cytokinesis protein family, whose members are guanosine nucleotide exchange factors for Rho GTPases. It has been confirmed as a SLE locus (rs11462616) in an Egyptian population [24]. Sheng et al [25] suggested that overexpression of the transcriptional regulator BACH2 represses Th9 cell differentiation by suppressing IRF4 expression in SLE patients, and that it might be a potential target for SLE treatment.…”
Section: Association Of Up-dppgcs In Pla-ko1l3 With Sle In the Gwas C...mentioning
confidence: 98%
“…To date, almost a hundred susceptibility loci have been linked with SLE through genome-wide association studies (GWAS), including the cytotoxic T lymphocyte associated protein-4 (CTLA4) and TNF receptor-associated factor-3 (TRAF3) [ 49 , 50 , 51 ]. CTLA4 modulates T cell activation, induces immune tolerance, as well as inhibits T cell proliferation dan differentiation, pro-inflammatory cytokines production and cell cycle progression [ 52 ].…”
Section: The Role Of Genetic Predisposition In the Pathogenesis Of Slementioning
confidence: 99%